Preclinical evaluation of tyrosine kinase 2 inhibitors for human beta-cell protection in type 1 diabetes - de Brachène, Alexandra Coomans (Diabetes Obes Metab, 2020)
AIM: Type 1 diabetes (T1D) is a chronic autoimmune disease leading to progressive loss of pancreatic beta cells. Interferon (IFN)-α plays a critical role in the crosstalk between pancreatic beta cells and the immune system in early insulitis. In human beta cells IFNα signals through JAK1 and TYK2, leading to endoplasmic reticulum stress, inflammation and HLA class I overexpression. IFNα, acting synergistically with IL-1β, induces apoptosis. Polymorphisms in TYK2 that decrease its activity are associated with protection against T1D, and we hypothesized that pharmacological inhibitors that specifically target TYK2 could protect human beta cells against the deleterious effects of IFNα. MATERIALS AND METHODS: Two TYK2 inhibitors provided by Nimbus Lakshmi were tested in human insulin-producing EndoC-βH1 cells and human islets to evaluate their effect on IFNα signalling, beta-cell function and susceptibility to viral infection using RT-qPCR, western blot, immunofluorescence, ELISA and nuclear dyes. RESULTS: The two TYK2 inhibitors tested prevented IFNα-induced human beta-cell gene expression in a dose-dependent manner. They also protected human islets against IFNα + IL-1β-induced apoptosis. Importantly, these inhibitors did not modify beta-cell function or their survival following infection with the potential diabetogenic coxsackieviruses CVB1 and CVB5. CONCLUSIONS: The two TYK2 inhibitors tested inhibit the IFNα signalling pathway in human beta cells, decreasing its pro-inflammatory and pro-apoptotic effects without sensitizing the cells to viral infection. The preclinical findings could pave the way for future clinical trials with TYK2 inhibitors for the prevention and treatment of type 1 diabetes.